The Effect of Discipline, Work Environment and OCB on Job Satisfaction of KUA Employees in Banyuwangi Regency - M. Fauzan Anshori; Suwignyo Widagdo; Diana Dwi Astuti (International Journal of Economics, Commerce, and Management, 2025)
Human Resource Management (HRM) is a strategic approach to managing the workforce within an organization, aiming to enhance both individual effectiveness and overall organizational performance. Job satisfaction plays a crucial role as a supplement for employees to maintain and carry out their jobs. When employees feel valued and heard, they tend to have higher intrinsic motivation, leading to improved performance. This research employs a quantitative approach with data collection techniques using questionnaires. The data analysis technique utilized is multiple regression analysis. The results of the study reveal that: Testing results indicate that discipline significantly affects the job satisfaction of employees at the Religious Affairs Office (KUA) in Banyuwangi Regency; Testing results indicate that the work environment significantly affects the job satisfaction of employees at the Religious Affairs Office (KUA) in Banyuwangi Regency; Testing results indicate that Organizational Citizenship Behavior (OCB) significantly affects the job satisfaction of employees at the Religious Affairs Office (KUA) in Banyuwangi Regency; Testing results indicate that discipline, work environment, and OCB collectively affect the job satisfaction of employees at the Religious Affairs Office (KUA) in Banyuwangi Regency. High discipline, supported by clear rules, can improve the job satisfaction of KUA employees in Banyuwangi Regency. Employees who feel comfortable in their workplace contribute to higher job satisfaction. Employees exhibiting strong OCB are more likely to experience greater job satisfaction. The synergy of high discipline, a conducive work environment, and strong OCB can significantly enhance the job satisfaction of KUA employees in Banyuwangi Regency.